FAKTOR PENYEBAB KERUSAKAN HUTAN MANGROVE DI DESA BURANGA KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Susilawati, Ni Gusti Kadek; Toknok, Bau; Korja, I Nengah (ForestSains, 2018)
Buranga Village is one of the villages that has extensive mangrove forests, but has been damaged over time. Therefore, it is necessary to conduct research on the Causes of Mangrove Forest Damage in Buranga Village, Ampibabo District, Parigi Moutong Regency. This study aims to determine the factors that cause damage to mangrove forests. The study was conducted in March - May 2017. This study used the Snowball sampling method in which the sample determination technique was initially small in number, then enlarged. Like a snowball that rolled a long time to become big. Samples taken amounted to 20 respondents. Observation parameters are water pollution (pa), abrasion (a), environmental stress, main livelihood, location of business land, utilization of firewood and perception of mangrove forest. The results showed that the damage to mangrove forests that occurred was more dominant due to the socio-economic factors of the local community compared to physical environmental factors can be seen from the total score that was done. In the socioeconomic factor of the community the Total Scoring Score is 230 and the Total Scoring Score on the physical environment factor was 100.